2020
DOI: 10.1590/1807-3107bor-2020.vol34.0036
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with toothache among Brazilian adults: a multilevel analysis

Abstract: The aim of this study was to evaluate the factors associated with toothache in the adult population of Minas Gerais, Brazil. Individual data from a population sample (age 35 to 44 years) were collected from a secondary database of the SB Minas survey. Sampling was carried out by clusters and with multiple drawing stages. The eligibility criteria were to reside in areas chosen for the research, be within the age group, and accept to participate in the research. The individual variables assessed by a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The prevalence of oral pain was similar to the range identified in a 2001 review of the literature [ 17 ] and to findings from more recent oral surveys in Brazil and South Africa [ 18 , 19 ]. Oral pain is considered a public health problem due to its frequency, impact on daily living, and the feasibility of prevention.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of oral pain was similar to the range identified in a 2001 review of the literature [ 17 ] and to findings from more recent oral surveys in Brazil and South Africa [ 18 , 19 ]. Oral pain is considered a public health problem due to its frequency, impact on daily living, and the feasibility of prevention.…”
Section: Discussionsupporting
confidence: 86%
“…The role of socioeconomic status in oral pain has already been demonstrated in different contexts [ 17 – 19 ]. Social disparities have been also identified historically; most socially vulnerable populations are at high risk of oral disease [ 11 , 21 ], and the barriers to accessing timely dental treatment increase the odds of oral pain [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 A study conducted in Brazil has shown that periodontal health status, such as probing depth greater than 3 mm, was associated with dental pain in adults. 11 This condition may perpetuate unhealthy oral habits that cause dental pain.…”
Section: Discussionmentioning
confidence: 99%
“…1 The literature reports that individual (behavioral) and contextual factors are associated with dental pain, especially with lower socioeconomic status. 2,10,11 This outcome is also more common in individuals with less access to primary healthcare and with a lower degree of social development measured by the Human Development Index (HDI). 12 Adolescence is the period of development between the ages of 10 and 19 years, 13 during which important biological and psychosocial changes occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation